2014
DOI: 10.1111/jsm.12344
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Characteristics and Unmet Needs of Men with Erectile Dysfunction: A Survey in Five European Countries

Abstract: Introduction Data suggest that ED is still an underdiagnosed and undertreated condition. In addition, it seems that men with ED are unsatisfied about their relationship with their physician and with the available drugs. Aim The study aims to identify health-related characteristics and unmet needs of patients suffering from erectile dysfunction (ED) in big 5 European Union (EU) nations (France, Germany, Italy, Spain, and UK). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 48 publications
2
84
0
Order By: Relevance
“…[48][49][50][51][52][53][54][55] ED may arise from an alteration of any of these components (precipitating event), but, eventually, it will involve all the others in a redundant way, having negative effects on quality of life, interpersonal relationships, and mood. [51][52][53][54] This complex, multidimensional, interactive model of ED pathogenesis captures the ever-changing, mutual influences of biology, marital and psychological life, and their contributions to the disturbance. Dissatisfaction and discontinuation of PDE5is might be the consequence of unrecognized psychological or relational issues underlying the sexual problem and not targeted by the medical treatment.…”
Section: Expert Opinionmentioning
confidence: 99%
“…[48][49][50][51][52][53][54][55] ED may arise from an alteration of any of these components (precipitating event), but, eventually, it will involve all the others in a redundant way, having negative effects on quality of life, interpersonal relationships, and mood. [51][52][53][54] This complex, multidimensional, interactive model of ED pathogenesis captures the ever-changing, mutual influences of biology, marital and psychological life, and their contributions to the disturbance. Dissatisfaction and discontinuation of PDE5is might be the consequence of unrecognized psychological or relational issues underlying the sexual problem and not targeted by the medical treatment.…”
Section: Expert Opinionmentioning
confidence: 99%
“…Despite being studied thoroughly in men over 40 years of age 18 , the prevalence of erectile dysfunction in younger men is rarely regarded as interesting 19,20 . In this context, a recent naturalistic study (a study in which the participant is observed without any manipulation by the researcher) reported that one man out of four seeking medical help for erectile dysfunction in the real-life setting is <40 years of age 21 .…”
Section: Epidemiologymentioning
confidence: 99%
“…26 Questions are divided into 5 domains: erectile function (6 items; maximum score, 30), orgasmic function (2 items; maximum score, 10), sexual desire (2 items; maximum score, 10), intercourse satisfaction (3 items; maximum score, 15), and overall satisfaction (2 items; maximum score, 10). Each question is rated from 0 to 5 (questions 1-10) or from 1 to 5 (questions [11][12][13][14][15], where higher values indicate less difficulty, greater frequency, more satisfaction, confidence, or enjoyment. For questions that focus on intercourse (ie, questions 1-10), "0" indicated that sexual intercourse had not taken place or was not attempted.…”
Section: Main Outcome Measuresmentioning
confidence: 99%
“…Factors underlying this connection remain unknown, 13 but both conditions have been associated with increased age, 2,14-16 comorbid disorders (eg, diabetes, 2,8,16 cardiovascular events, 17,18 radical prostatectomy 19,20 ), psychological symptoms, [9][10][11]15,21,22 and altered blood flow. 13 In addition, ED has been associated with depression, 22 which, similar to PD, may influence a patient's assessment of physical and psychological functioning.…”
mentioning
confidence: 99%